Groundspotting in the tourist space of Łódź - Łuć, Bartłomiej (Percepcja turystyki w przestrzeni i w czasie pandemii COVID-19, 2022)
In the last few years, an increase in the popularity of sports tourism has been noticeable. Among its types, fan tourism is distinguished, i.e. related to visiting sports-related tourist attractions and one of its forms is ‘groundspotting’ which refers to visiting stadiums outside of match times or other organized sporting events. Groundspotting also functions in the tourist space of Łódź. In this article, the author has analyzed how groundspotting affects sports tourism in Łódź. The research methods he used were an investigation of the literature and source materials developed by sports facilities and museums thematically related to sport. The conducted research has shown that groundspotting is found in the tourist space of Łódź, however it is of little importance and the prospects for its development are not optimistic.